AI-Augmented Netnography of Public Sentiment in Aqua Ethical Controversy - Mario Sudianto Chien (Cv. Syntax Corporation Indonesia, 2026)
The rapid spread of social media has heightened public scrutiny of corporate ethical practices, especially during crises. In October 2025, Aqua (Tirta Investama) was involved in an ethical scandal regarding groundwater extraction, which contradicted its long-established branding as natural mountain spring water, raising concerns about ethical marketing, environmental sustainability, and corporate responsibility. This research aims to analyze public attitudes toward Aqua’s ethical scandal and explore how public sentiment impacts corporate legitimacy and sustainability, while contributing theoretically to the intersection of digital ethics, stakeholder theory, and netnography. The study adopts a qualitative approach using AI-augmented netnography, combining traditional netnographic analysis with artificial intelligence tools that integrate natural language processing (NLP) in sentiment classification, thematic analysis, clustering, and interpretation. The sample consists of 770 original comments gathered from three posts on Aqua’s Instagram account released during the peak of public attention. The results reveal that 70.13% of comments were negative; five dominant themes emerged: brand trust crisis, deceptive marketing, environmental degradation, labor welfare, and corporate responsibility. The controversy was perceived as a moral failure, weakening Aqua’s credibility and social legitimacy. This study demonstrates how social media discourse can transform an ethical controversy into a legitimacy issue with long-term sustainability implications, highlighting the importance of transparent marketing, responsible resource management, and effective stakeholder communication to maintain corporate trust in the digital age.